Impact of External Debt Management on Economic Growth of Nigeria - Ogbonna Ogbonna; Ihemeje Ihemeje; Obioma Obioma; Hanson Hanson; Amadi Amadi (Journal La Bisecoman, 2021)
This study examined the impact of External debt management on economic growth of Nigeria. Using annual time series data collected over the period of 33 years (1986 – 2018). The data for the study were collected from the CBN statistical bulletin annual report. The variables on which data are collected include: Real Gross Domestic Product, External Debt, External Debt service, Balance of Payment and Exchange Rate. Data were analyzed using the Ordinary least squares (OLS) multiple regression analysis. It proceeded with Descriptive statistics; Augmented Dickey Fuller (ADF) unit root test, Co-integration test and Auto-Regressive Distributed Lag (ARDL). The study revealed that impact of external debt management on economic growth of Nigeria over the period under review was statistically significant with external debt, external debt service payment and balance of payment but statistically insignificant with exchange rate. The study recommended that governments should establish and adopt an optimal balance between external debt acquisition and application /allocation of the acquired funds to productive projects for the purpose of making a high output and a steady economic growth. The management should live up to expectation by encouraging efficient commitment of borrowed funds to productive projects so as to comply with debt serving agreement and outright payments, measures such as improving exports should be implemented to ensure that local currencies are stable.